دکنی ادب کی تفہیم کے مسائل اوردکنی اردوکی لغات - Rauf Pareikh (Tabeer e Nau, 2025)
Dakani is a regional variety of Urdu spoken in Deccan, that is, certain parts of south India. With the passage of time, Dakani developed its innate, local peculiarities that make it quite different from Urdu spoken in Northern India and elsewhere. Several Indo-Aryan languages and dialects from North, especially Khari Boli, Haryani, Marathi, Gujarati and some local Dravidian dilaects, have influenced Dakani and its literature. Dakani has not only borrowed vocaulary from these languages and dialects but Dakani's own typtical pronunciation of Urdu words and orthographic deviations have made reading and understanding Dakani texts quite difficult to understand. Since Urdu's earliest literary texts were written in Dakanai, it is of utmost importance to understand these texts. To make undertand these texts easier for scholars and common readers, some dictionaries were compiled. This article first analyses the reasons that have made understanding Urdu's earliest texts written in Dakani more difficult, for example, words borrowed from other languages, local pronunciation of Urdu words, Urdu words written in different calligarphic style and standard, as well as differnt spelling rules , etc. The article then describes and evaluates some dictionaries of Dakani Urdu, compiled to facilitate the understanding of Dakani texts. It lists the earliest such dictionary written in 1935 and the latest one published in 2008, analyzing their worth according to lexicographical principles.